REAKSI PENATAAN ULANG SIGMATROPIK HIDROGEN [1,3] SECARA TERMAL DAN REAKSI PENATAAN ULANG PROTOTROPIK [1,3] YANG DIKATALISIS OLEH KATALIS TRANSFER FASE (PTC) , [18]-CROWN ETHER-6: SEMI-SINTESIS VANILI DARI EUGENOL* - Suwarso, Wahyudi Priyono; Sukri, Tony; Wijaya, Hendra (UI Scholars Hub, 2002)
Semi-synthesis of vanillin from eugenol can be divided into two step reactions namely, isomerization of eugenol into isoeugenol, and cleavage oxidation of isomerization product into expected reaction product (vanillin). In this work isomerization of eugenol or eugenyl acetate into isoeugenol or isoeugenyl acetate has been done via the following reactions: (1) Sigmatropic hydrogen (1,3) thermalic rearrangement reaction: direct heating of eugenol or eugenyl acetate at 220o C for 8 hours can produce 52.2% of isoeugenol or 65.7% of isoeugenyl acetate (both chemical yields are measured by means nmr-spectrometer), where products are viscose yellow-brownish liquid as mixture of unseparated starting material and isomerization product. (2) Prototropic (1,3) rearrangement catalyzed by phase transfer catalyst (PTC): (18)-crown ether-6 at room temperature can be afforded 71.4% of isoeugenol as light yellow liquid (mixture of unseparated starting material and isomerization product). Without any separation of mixture between isomerization product and starting material followed by subsequent cleavage oxidation using KMnO4 as oxidator in neutral condition catalyzed by phase transfer catalyst: (18)- crown ether-6 at room temperature for 3 hours can be yielded 16.5-22.9% of vanillin (from the starting material; eugenol or eugenyl acetate). The spectroscopical data of synthetical vanillin is not rather different with the spectroscopical data of authentical natural vanillin